ADAPTIVE REARRANGEMENTS OF STRUCTURAL COMPONENTS IN THE ADULT RATS’ ADENOHYPOPHYSIS AFTER LONG-TERM EXPOSURE TO HEAVY METAL SALTS - Hryntsova, N.B.; Romaniuk, A.M.; Bumeister, V.I.; Sikora, K.O. (World of Medicine and Biology, 2024)
The article presents the results of the morphofunctional rearrangements’study of the adenohypophysis’ structural components of sexually mature rats after long-term exposure to heavy metal salts and an adaptive period of 90 days. General morphological, morphometric, immunohistochemical and statistical research methods were used. A long-term period of adaptation to the heavy metal salts’ exposure significantly improved the condition of the adenohypophysis’structural components: the swelling of the gland and the expressiveness of the connective tissue component decreased, the condition of the rheological properties of blood, histoarchitectonics, the condition of adenocytes and their secretory activity improved, the level of expression of HSP90 in the cytoplasm of adenocytes increased to strongly positive, disappeared processes of cyst formation, the tension of compensatory and adaptive processes decreased. The above-mentioned morphofunctional rearrangements had a positive effect on the processes of the hormones’evacuation into blood, the course of the general adaptation syndrome and the restoration of homeostasis in the organ and the body as a whole.